Ultrasensitive flexible wearable pressure/strain sensors: Parameters, materials, mechanisms and applications - Sharma, A.; Ansari, M. Z.; Cho, C.
Wearable technology has led to a rapid development of flexible sensors with numerous applications especially in human motion monitoring. The utmost requirement of wearable technology is that of flexibility and sensitivity which is hard to achieve with traditional sensors. In this research article, we aim to review the latest novel advancements in materials, sensing mechanisms, synthesis and applications of wearable flexible pressure/strain sensors in terms of their key operational parameters such as sensitivity, linearity, working range, hysteresis and stretchability. Prevalent piezoresistive, piezoelectric, and capacitive sensing mechanisms are reviewed comprehensively. Some innovative techniques such as inclusion of micro-structures on the sensing layer, porous dielectric layer and a 3D monolith/foam-based approaches are also discussed. Since the material properties plays an important role in flexible sensors, current emerging materials in the field of flexible sensors such as MXene, hydrogels, graphene and carbon nanotubes has been discussed in details along with already employed material such as conducting polymers. In the end, the applications related to human motion monitoring and electronic skin with flexible wearable sensors are discussed as presented in various articles. Finally, we discuss the challenges along with the future scope for the development of flexible wearable sensors.
Keywords: FLEXIBLE SENSORS; WEARABLE DEVICES; PIEZORESISTIVE; WEARABLE FLEXIBLE SENSORS; HUMAN MOTION MONITORING; ELECTRONIC SKIN